Multi-modal strain and temperature sensor by hybridizing reduced graphene oxide and PEDOT:PSS. (8th February 2020) - Zhang, Fan; Hu, Hailong; Islam, Mohammad; Peng, Shuhua; Wu, Shuying; Lim, Sean; Zhou, Yang; Wang, Chun-Hui
Abstract: Mechanically stretchable sensors are responsive to multiple stimuli, such as strain and temperature, making it difficult to identify individual stimulus using a single senor. Herein, we present a hybrid sensor featuring dissimilar impedance frequency-responses under different stimuli. The sensor is made by infusing polydimethylsiloxane (PDMS) into an aerogel containing a hybrid of conductive materials consisting of PEDOT:PSS and reduced graphene oxide. Exhibiting positive and negative sensitivity to strain and temperature, respectively, this sensor makes it possible to determine both stimuli using an impedance method. By measuring the sensor's electrical impedance at two different frequencies, both strain and temperature can be readily determined using just one sensor. Test results under long-term cyclic loading confirm that the hybrid sensor also retains high sensitivity, stretchability, and cyclic stability. The new impedance method used in conjunction with the hybrid sensor enable simultaneous determination of multiple stimuli, such as strain and temperature.